Exchange rates and oil price under uncertainty and regime switching: A Markov-switching VAR approach - Nagmi Moftah Aimer; Abdulmula Albashir Lusta (Universitas Islam Indonesia, 2021)
Purpose - This paper analyses the effects of the US economic policy uncertainty index and oil price changes on the dollar exchange rate over a monthly period from January 2006 to August 2020.Methods - This paper uses the Markov-switching Vector Auto-Regressive (VAR) model.Findings - The results show that the sharp decline regime in the exchange rate is the most stable. In addition, the impact of the oil price on the exchange rate of the concerned currencies is stronger than the effect of EPU on the exchange rate of these currencies. We also find that most of the effects of oil prices were negative, while positive for the Canadian dollar and the Japanese yen exchange rate.Implications - Addressing this investigation contributes to many of the areas covered in recent macroeconomic and finance research. Moreover, such research can help predict changes in currency and oil prices better and create profitable investment and hedging strategies for currencies and oil.Originality - We consider the effect of economic policy uncertainty (EPU) and oil price changes on the relationships between those markets and study these relationships under different market conditions.